ACCOUNTING TERMINOLOGY. - Preinreich, Gabriel A. D. (The Accounting Review, 1933)
Whereas the terminology of law or medicine is intended to serve primarily if not exclusively the members of those learned professions, the accountants' language must be understood by everybody who has occasion to refer to financial statements. Professional jargon is utterly out of place. Editors of accountants' dictionaries should have desired to make their publications as comprehensive as possible, including not only terms current in business life, but also miscellaneous additional information which might be useful to accountants and business men in general. British usage as well as all words used in their ordinary sense should be omitted or at most, listed with a reference to standard dictionaries. Commonly used terms, which differ from a defined term only by a self-explanatory adjective were also to he excluded. The terminology committee of the American Institute of Accountants has no higher goal than that negative recompense which, according to Dr. Johnson, is the only one that lexicographers can ever hope to attain, namely to escape reproach.